FOURIER CAUSALITY AND VOLATILITY SPILLOVER PERSPECTIVES TO ANALYZE THE EFFECT OF TERRORISM ON TURKISH AND EUROPEAN STOCK MARKETS - Adnan Hushmat (International Journal of Business Reflections, 2023)
Terrorism has become a curse for most of the underdeveloped economies. Even relatively developed regions like Europe and Turkey are struggling to combat it. Besides the economic and political consequences, terrorist activities also have psychological cost that may reflect in stock market. This study investigates the causal effects of systematic shocks on mean returns and volatility of the general and 14 sectoral indices in Europe and Turkey using contemporary causality tests like Fourier Toda-Yamamoto Causality test (Nazlioglu et al., 2016), Fourier Standard Granger Causality test (Enders and Jones, 2015), and Causality in Variance (Hafner and Herwartz, 2006). Tourism related sectors turn out to be fragile whereas financial sector have significant resilience to terrorist attacks. Moreover, the spillover analysis shows that the Turkish stock market turns out to be more fragile to terrorist attacks in Europe than the other way around.